Body mass index, obesity, and prevalent gout in the United States in 1988–1994 and 2007–2010. Issue 1 (27th December 2012) - Juraschek, Stephen P.; Miller, Edgar R.; Gelber, Allan C.
Abstract Objective To determine the association and prevalence of gout among overweight, obese, and morbidly obese segments of the US population. Methods Among participants (age ≥20 years) of the National Health and Nutrition Examination Surveys in 1988–1994 and 2007–2010, gout status was ascertained by self‐report of a physician diagnosis. Body mass index (BMI) was examined in categories of <18.5 kg/m2, 18.5–24.9 kg/m2, 25–29.9 kg/m2, 30–34.9 kg/m2, and ≥35 kg/m2 and as a continuous variable. The cross‐sectional association of BMI category with gout status was adjusted for demographic and obesity‐related medical disorders. Results In the US, the crude prevalence of gout was 1–2% among participants with a normal BMI (18.5–24.9 kg/m2), 3% among overweight participants, 4–5% with class I obesity, and 5–7% with class II or class III obesity. The adjusted prevalence ratio comparing the highest to a normal BMI category was 2.46 (95% confidence interval [95% CI] 1.44–4.21) in 1988–1994 and 2.21 (95% CI 1.50–3.26) in 2007–2010. Notably, there was a progressively greater prevalence ratio of gout associated with successively higher categories of BMI. In both survey periods, for an average American adult standing 1.76 meters (5 feet 9 inches), a 1‐unit higher BMI, corresponding to 3.1 kg (∼6.8 pounds) greater weight, was associated with a 5% greater prevalence of gout, even after adjusting for serum uric acid (P < 0.001). Conclusion Health care providers should be aware of the elevated burden of gout among both overweight and obese adults, applicable to both women and men, and observed among non‐Hispanic whites, non‐Hispanic African Americans, and Mexican Americans in the US.